Shock and Materials - Batsanov, Stepan S. (Engineering Materials,, 2018)
This book highlights how the properties and structure of materials are affected by dynamic high pressures generated by explosions, projectile impacts, laser compression, electric discharge or ball milling. Starting with the basics of shock-wave physics and an outline of experimental techniques, it then surveys dynamic compressibility and equations of state of various substances, phase transitions and syntheses of novel compounds under shock. It covers various industrial applications including hardening of metals and grinding (fragmentation) of solids, saturation of solids with defects for use as catalysts, production of superhard materials (synthetic diamond, BN (boron nitride)) and nanomaterials, especially nanodiamond, and discusses state-of-the-art techniques such as combining dynamic and static compression to obtain monolithic materials.